Self‐Healing Carbon Fiber–Reinforced Polymers for Aerospace Applications - Surawut Chuangchote; Methawee Nukunudompanich (My University, 2022)
Self-healing carbon fiber–reinforced polymers (CFRPs) have been explored in-depth since the 2000s. Microcapsules, vascular networks, dissolved thermoplastics, and reversible interactions can be used to give polymer matrix composites with self-healing properties. Recent improvements, particularly epoxy employed as a matrix phase in carbon fiber–reinforced polymers, are chosen and examined in terms of their repair mechanisms, validation testing methods, and any other attributes that might be relevant in aerospace applications. Extrinsic self-healing, which is pioneered in this field, paves the way for more modern approaches that take advantage of intrinsic self-molecular healing pathways. The latter appears to be the more promising self-healing carbon fiber–reinforced polymers in the long run. Self-healing carbon fiber–reinforced polymers are critical for increasing aircraft fatigue, impact, and corrosion resistance. Complex aviation composite geometries that are formerly made using time-consuming and expensive techniques (e.g. autoclave) can now be made utilizing simpler (and hence less expensive) processes, such as co-electrospinning, vacuum-assisted injection molding, or hand-lay up molding. Engines, fuselages, and aerostructures, as well as anticorrosion coatings, have profited from the usage of self-healing carbon fiber–reinforced polymers. Each area demands its own set of processes for improvement. Anyhow, carbon fiber–reinforced polymers face some problems of disposal and recycling.
Keywords: Polymer composites and self-healing; Fuel Cells and Related Materials; Surface Modification and Superhydrophobicity